IMPACT OF INDOOR AIR COMPOUNDS ON PERFORMANCE, INCLUDING THE RELATION BETWEEN AIR COMPOUNDS AND COGNITIVE PERFORMANCE - Mashita, Firla Elok; Zein, Syahru; Marti'ah, Siti (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Indoor air quality (IAQ) is identified as a primary determinant of cognitive performance, psychological well-being, and academic success among students. A comprehensive systematic review of literature published between 2000 and 2026 evaluated the accumulation of anthropogenic and ambient-derived pollutants, including carbon dioxide (CO2), particulate matter (PM2.5/PM10), volatile organic compounds (VOCs), and carbon monoxide (CO). Evidence showed that educational environments characterized by high occupancy and inadequate ventilation frequently lead to elevated CO2 concentrations exceeding 1500 ppm, which are robustly associated with diminished executive functions. Analysis revealed that particulate matter significantly increases error rates in attention-intensive tasks, while subclinical CO exposure is linked to heightened psychological distress and emotional lability. Furthermore, high TVOC levels were found to reduce task precision by approximately 5%. The integration of strategic environmental interventions, such as high-efficiency filtration and optimized air exchange, effectively mitigates these risks and enhances standardized assessment scores. Standardized IAQ monitoring remains essential as a cost-effective strategy to improve students' learning trajectories and ensure long-term academic competitiveness in higher education admissions.